Optimisme saat pandemi: strategi storytelling pada video promosi destinasi pariwisata super prioritas - Dian Nuranindya; Agustinus Rusdianto Berto; Anabel Yevina Mulyadi Wahyu (Faculty of Communications Science, Dr. Soetomo University, 2023)
As domestic tourist arrivals begin to grow amid the easing of the Covid-19 pandemic in Indonesia, the Ministry of Tourism and Creative Economy (Kemenparekraf) of the Republic of Indonesia is optimistic about the revival of the tourism sector in 2021. For this reason, the Ministry of Tourism and Creative Economy produces promotional videos for Wonderful Indonesia storytelling style that prioritizes super priority tourist destinations. This study aims to evaluate the use of digital storytelling strategies in promotional video content for Lake Toba, Lombok, Labuan Bajo, and Borobudur. The exploratory sequential mixed methods design was used to obtain qualitative and quantitative data. Based on directed qualitative content analysis using the concept of storytelling heroes journey structure, the four video contents highlight the domination of hero characters in the story structure. However, the most complete content of heroic characters is found in the video for the destination of Borobudur, rather than Lake Toba, which has the highest production costs. Then, based on the results of experimental validation of the findings of previous qualitative data, it was found that the digital storytelling technique used was able to moderately influence the positive image of the four destinations. Digital storytelling for tourism promotion videos in the future needs to integrate the complete structure of heroic stories by involving a variety of supporting characters, both protagonists and antagonists, as well as incorporating elements of economy and pacing in the content